Effects of Radiation on the Protein and DNAContent inGenistein Treated Swiss Albino Mice: Protection of DNAand protein by genistein against radiation - Ajay Gaur,; Arvind Lal Bhatia, (Iranian Journal of Pharmaceutical Sciences, 2009)
Genistein is a soya isoflavone, which is found naturally in legumes, such as soybeans and chickpeas. The intraperitoneal administration of the optimum dose (200mg/kg) of genistein 24 h and 15 minbefore irradiation (8 Gy at a dose rate of 1.02 Gy/min) recovered the deficit in protein content (28.63±1.44%) and the DNA content (21.61±8.19%) if an average of 5 intervals of autopsies 1st, 3rd, 7th, 15th and 30thdays are taken into consideration as compared to those of control group in Swiss albino mice. The decrease of protein amount after irradiation may be due to its lysis by gamma radiation or may be at the synthesis level or it may be due to the depression of enzymes involved in the activation of amino acids and transferring to tRNAor by the inhibition of release of synthesized polypeptides from polysomes.The decrease in DNAcontent after irradiation is due to an inhibition of replication of this compound in nucleus and accumulation of ribonucleotide in the cytoplasm,which is based on the inability, of irradiated cell to reduce ribonucleotide to DNA in the nucleus. The results indicate that genistein against radiation effect may pave way to the formulation of medicine in radiotherapy for normal tissue.